Reversible natural language watermarking using synonym substitution and arithmetic coding - Hao, Wei (2019)
For protecting the copyright of a text and recovering its original content harmlessly, this paper proposes a novel reversible natural language watermarking method that combines arithmetic coding and synonym substitution operations. By analyzing relative frequencies of synonymous words, synonyms employed for carrying payload are quantized into an unbalanced and redundant binary sequence. The quantized binary sequence is compressed by adaptive binary arithmetic coding losslessly to provide a spare for accommodating additional data. Then, the compressed data appended with the watermark are embedded into the cover text via synonym substitutions in an invertible manner. On the receiver side, the watermark and compressed data can be extracted by decoding the values of synonyms in the watermarked text, as a result of which the original context can be perfectly recovered by decompressing the extracted compressed data and substituting the replaced synonyms with their original synonyms. Experimental results demonstrate that the proposed method can extract the watermark successfully and achieve a lossless recovery of the original text. Additionally, it achieves a high embedding capacity.